Tampilan Penerapan Sistem Enterprise Resource Planning (ERP) dalam Uji Coba Software ODOO Pada PT. BRS - Noviyanti Noviyanti; Shelvia Ayu Kintami (CV. ITTC INDONESIA, 2025)
Abstract This research aims to plan the implementation of Enterprise Resource Planning (ERP) using odoo software at PT.BRS. PT BRS is a service company in the field of mining consulting. The main emphasis of this research is on the importance of building a more precise and efficient system implementation planning process, taking into account the various obstacles faced by the company when handling manual sales records, including the potential for incorrect data entry, human error, and delays in carrying out sales operations at PT. BRS. The method used in planning the ERP system implementation is Accelerated SAP (ASAP). The configuration of the Odoo ERP system used is the sales and accounting module. Black box testing on this system test is carried out to verify that the system operates in accordance with the specifications set and accurately processes the input given correctly. The results of system testing using black box testing show that business processes can run as expected and according to user needs.